Open-access endoscopy service for general practitioners. - Holdstock, G (1979)
An open-access general-practitioner referral service for endoscopy of the upper gastrointestinal tract was established in a district general hospital, and the impact of the service over three years was assessed. The reason for referral, duration of symptoms, and amount of disease detected were the same in patients referred by general practitioners and those attending from hospital outpatient departments. Despite a steady increase in the number of patients referred for endoscopy, the number of barium-meal examinations performed did not correspondingly decrease. The number of ulcers and cancers detected in each six-month period of the study did not increase, and the combined overall pick-up rate for these two conditions fell from 25% to 13%. All general practitioners in the area were sent questionnaires. Most thought that clinic referral had been reduced and patient management helped as a result of the introduction of the service. While the value of negative endoscopic findings cannot be assessed, there is little objective evidence of benefit. Hence the large increase in numbers of endoscopies performed as a result of the introduction of the service cannot be justified.